Molecular Identification of Color Variants of Procambarus clarkii Using the COI Gene for Taxonomic Validation - Dian Bhagawati; Muhammad Husein Sastranegara; Agus Nuryanto; Anastasia Endang Pulungsari; Elly Tuti Winarni; Atang; Hanan Hassan Alsheikh Mahmoud (Advance Sustainable Science Engineering and Technology, 2025)
This study addresses taxonomic uncertainty surrounding color variants of Procambarus clarkii in aquaculture and conservation contexts. We investigated whether commercially significant color morphs represent distinct subspecies or phenotypic variations of a single species. Using the cytochrome c oxidase subunit I (COI) gene as a molecular marker, we analyzed four color morphs (blue, white, orange, and brown) from aquaculture facilities in Banyumas Regency. DNA extraction, PCR amplification, and sequencing were performed on 20 specimens. Results showed high sequence homology (98.7-99.8%) across all variants, confirming they belong to a single species. Genetic distance analysis revealed minimal divergence (0.2-1.3%), insufficient for subspecies classification. Phylogenetic reconstruction demonstrated specimens clustered by genetic similarity rather than color or geographic origin, indicating coloration results from genetic mutations rather than environmental adaptations. This COI-based approach provides a molecular framework for taxonomic classification of P. clarkii varieties, with implications for breeding programs, variety certification, and management of this economically important yet potentially invasive species.